(untitled) (Journal of Pakistan Orthopaedic Association, 2021)
Objective: To determine the severity and pattern of bony injuries among the victims of motor bike motorbike accidents presented to the Accident and Emergency Department of Dr. Ruth K.M Pfau Civil Hospital Karachi. Methods: This descriptive study was conducted in Dr. Ruth K.M Pfau Civil Hospital Karachi from 12th January 2019 to 12th January 2020. All adult patients of motorbike accidents with extremity fractures fulfilling the inclusion criteria were included in this study. In the included subjects the locations of fracture or dislocation and whether closed or open were noted. Results: The total number of patients were 380 with mean age of 28.67 ± 12.07 years. Lower extremity fractures were noted in 273(71.8%) patients and upper extremity in 107(28.1%) patients. Tibia fibula was the commonest lower limb fracture documented in 157(41.3%) patients while radius was the commonly fractured upper limb bone in 46(12.1%) patients. Majority (75.2%, n=286) of the fractures were closed while open fractures were seen in 94(24.7%) patients. Conclusion: Victims of motorbike accidents sustained variable bony injuries. Majority of these fractures were closed. Tibia fibula was the commonest bone fractured.